Nitrate-Dependent Iron Oxidation: A Potential Mars Metabolism - Price, Alex; Pearson, Victoria K.; Schwenzer, Susanne P.; Miot, Jennyfer; Olsson-Francis, Karen (Frontiers in Microbiology, 2018)
This work considers the hypothetical viability of microbial nitrate-dependent Fe2+ oxidation (NDFO) for supporting simple life in the context of the early Mars environment. This draws on knowledge built up over several decades of remote and in situ observation, as well as recent discoveries that have shaped current understanding of early Mars. Our current understanding is that certain early martian environments fulfill several of the key requirements for microbes with NDFO metabolism. First, abundant Fe2+ has been identified on Mars and provides evidence of an accessible electron donor; evidence of anoxia suggests that abiotic Fe2+ oxidation by molecular oxygen would not have interfered and competed with microbial iron metabolism in these environments. Second, nitrate, which can be used by some iron oxidizing microorganisms as an electron acceptor, has also been confirmed in modern aeolian and ancient sediment deposits on Mars. In addition to redox substrates, reservoirs of both organic and inorganic carbon are available for biosynthesis, and geochemical evidence suggests that lacustrine systems during the hydrologically active Noachian period (4.1–3.7 Ga) match the circumneutral pH requirements of nitrate-dependent iron-oxidizing microorganisms. As well as potentially acting as a primary producer in early martian lakes and fluvial systems, the light-independent nature of NDFO suggests that such microbes could have persisted in sub-surface aquifers long after the desiccation of the surface, provided that adequate carbon and nitrates sources were prevalent. Traces of NDFO microorganisms may be preserved in the rock record by biomineralization and cellular encrustation in zones of high Fe2+ concentrations. These processes could produce morphological biosignatures, preserve distinctive Fe-isotope variation patterns, and enhance preservation of biological organic compounds. Such biosignatures could be detectable by future missions to Mars with appropriate instrumentation.